PENGARUH KONSENTRASI KOH TERHADAP SIFAT FISIS DAN ELEKTROKIMIA ELEKTRODA KARBON DARI LIMBAH KULIT DURIAN SEBAGAI SEL SUPERKAPASITOR - Pandi Kurniawan; Erman Taer; Usman Malik; Rika Taslim (Universitas Riau, 2018)
Activated carbon electrode have been prepare from durian shell focused in KOH concentration variations at chemical activation process. The preparation of carbon electrodes begins with pre-carbonization process, grinding using Hard Grinder and ball milling, after that followed by sieving process with particle size at range of 39 - 52 μm. Chemical activation was performed by using KOH activator agent with concentration variation of 0.5 M, 0.6 M, 0.7 M. Carbon powder are formed to pellet form using Hydraulic Press at a 8 ton compression pressure. The carbonization process is carried out a temperature of 600°C in the N2 gas atmosphere at a temperature of 900°C for 2 hours. The electrodes characterization are performed to determine the physical and electrochemical properties.The physical properties such as density, degree of cristanility, surface morfology was analyzed by calculate the electrode dimension such as, mass, thickness and diameter, X-ray diffraction analysis and Scanning Electron Microscopy Analysis. the electrochemical properties was studied the cell capacitance and the electrode capacitance specific using Cyclic Voltammetry method. the electrode density were decrease with the increasing the KOH concentration. The smallest density has been found at electrode using a KOH concentration of 0.7 M. The XRD test showed a carbon was amorfphuse structure identified by existing two broadening peaks at an angle of 2θ, ie 24.967°, 44.315° and 81.332° which describes the (002), (100) and (112) planes. Furthermore, samples were analyzed by Scanning Electron Microscopy and X-ray diffraction. The cyclic voltammetry result, obtained the highest specific capacitance of 89.05 F/g and cell capacitance 24,04 F was found at electrode with a KOH concentration of 0.7 M. From this research it can be concluded that the KOH optimum concentration was 0.7 M.